Mitochondrial Protective Properties Exerted by Jm-20 in a Dementia Model Induced by Intracerebroventricular Administration of Streptozotocin in Mice - Wong-Guerra, M (Elsevier B.V., 2025)
Background: Mitochondrial dysfunction and brain insulin resistance have been related to Alzheimer s disease (AD) development. Streptozotocin (STZ) is commonly employed to disrupt glucose and insulin metabolism, even causing cognitive impairment in animal models. We aimed at studying the protective effect of JM-20 on STZ-induced memory impairment and brain mitochondrial dysfunction. Methods: Male C57Bl6 mice received 3 mg/kg STZ intracerebroventricularly and JM-20 (0.25 mg/kg or 4 mg/kg) was administered daily by gastric gavage. Episodic memory was evaluated through Y-maze, novel object recognition, and Morris water maze. Endogenous antioxidant systems (catalase and superoxide dismutase activities), total sulfhydryl groups, malondialdehyde levels were also studied and acetylcholinesterase (AChE) activity were assessed in the prefrontal cortex (PC) and hippocampus (HO). Results: demonstrated that STZ injection impaired recognition and spatial learning and memory and oxygen flow in all mitochondrial respiration states. Additionally, STZ increased AChE, superoxide dismutase, and catalase activity in the PC but not in HO tissue. A neuroprotective effect of JM-20 on STZ-induced memory decline, and mitochondrial dysfunction was observed, suggesting an important causal interaction. In addition, JM-20 was able to decreased AChE enzyme hyperactivity, rescued endogenous antioxidant systems, and prevented histologically observed neuronal damage Conclusion: Our results indicate that JM-20 protects against STZ-induced impairment in brain bioenergetic metabolism and memory, confirming its potential as a candidate for treating neurodegenerative disorders associated with mitochondrial dysfunction like AD. © 2024 Elsevier B.V.
Keywords: Brain mitochondria; Dementia; JM-20; Neuroprotection; STZ icv